PENINGKATAN KEMAMPUAN MENULIS TEKS EKSPOSISI MELALUI MODEL ASSURE PADA SISWA KELAS XB SMAS GKST PALU - Christi L., Rita; Nur, Yunidar; Syamsuddin, Syamsuddin (BAHASANTODEA, 2016)
This research have the purpose to improve ability and to explain the improvement of students study result at the tenth B grade students of SMAS GKST Palu used assure model. This research was classroom action research with the subject of the research was tenth B grade students of SMAS GKST Palu. This research have done in the two cycles, each of cycle used assure model. Result of this research showed that the using of assure model in writing exposition text. It seen at the improvement of the students ability in each cycle. Based on the assesment result of each action, it was obtained the average score of cycle I, there was the average score of students writing ability 72 (low) with the percentage of classical study completeness 58%, whereas at the cycle II, the average score of students writing ability 84 (High) with the percentage of classical study completeness 89%. This result showed that the using of assure model in writing exposition text was succes and have and itÂ  can improve writing ability at the tenth B grade students of SMAS GKST Palu.